12.2k views
5 votes
Simplify: (3x2 - 4x+6) + (7x-2)

OA. 3x2 + 3x + 4
OB. 3x2-11X-8
OC. 3x2 + 11x + 4
OD.
10.x2 - 6x + 6

User Jozef Izso
by
4.3k points

2 Answers

4 votes

Answer:


3x^(2) +3x+4

Explanation:

1.)Remove the parentheses
3x^(2)-4x+6+7x-2

2.)Group like terms

3.)Add similar elements -4x-7x=3x =
3x^(2)+3x+6-2

4,)Add/Subtract the numbers 6-2=4

5.)
=3x^(2) +3x+4

:)Hope you enjoy this:)

User Lars Knickrehm
by
5.4k points
7 votes

Answer:

3x^(2)+3x+4

Explanation:

User Daniel Rose
by
5.2k points